PRMT5 Circular RNA Promotes Metastasis of Urothelial Carcinoma of the Bladder through Sponging miR-30c to Induce Epithelial-Mesenchymal Transition - Chen, Xin; Chen, Ri-Xin; Wei, Wen-Su; Li, Yong-Hong; Feng, Zi-Hao; Tan, Lei; Chen, Jie-Wei; Yuan, Gang-Jun; Chen, Si-Liang; Guo, Sheng-Jie; Xiao, Kang-Hua; Liu, Zhuo-Wei; et al. (Clinical cancer research, 2018)
Circular RNAs (circRNAs), a novel class of noncoding RNAs, have recently drawn lots of attention in the pathogenesis of human cancers. However, the role of circRNAs in cancer cells epithelial-mesenchymal transition (EMT) remains unclear. In this study, we aimed to identify novel circRNAs that regulate urothelial carcinoma of the bladder (UCB) cells' EMT and explored their regulatory mechanisms and clinical significance in UCBs. We first screened circRNA expression profiles using a circRNA microarray in paired UCB and normal tissues, and then studied the clinical significance of an upregulated circRNA, circPRMT5, in a large cohort of patients with UCB. We further investigated the functions and underlying mechanisms of circPRMT5 in UCB cells' EMT. Moreover, we evaluated the regulation effect of circPRMT5 on miR-30c, and its target genes, and , in two independent cohorts from our institute and The Cancer Genome Atlas (TCGA). We demonstrated that upregulated expression of circPRMT5 was positively associated with advanced clinical stage and worse survival in patients with UCB. We further revealed that circPRMT5 promoted UCB cell's EMT via sponging miR-30c. Clinical analysis from two independent UCB cohorts showed that the circPRMT5/miR-30c/SNAIL1/E-cadherin pathway was essential in supporting UCB progression. Importantly, we identified that circPRMT5 was upregulated in serum and urine exosomes from patients with UCB, and significantly correlated with tumor metastasis. CircPRMT5 exerts critical roles in promoting UCB cells' EMT and/or aggressiveness and is a prognostic biomarker of the disease, suggesting that circPRMT5 may serve as an exploitable therapeutic target for patients with UCB.